THE IMPACT OF BUSINESS SOCIAL RESPONSIBILITY ON EMPLOYEE PERFORMANCE: THE MANAGEMENT DIMENSION - BUKHALO, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The aim of the article is to conduct a comprehensive study of the relationship between corporate social responsibility (CSR) and employee performance from a managerial perspective, as well as to justify mechanisms and practices that enable the integration of CSR principles into human resource management systems in order to enhance motivation, engagement, and productivity. Within the scope of this aim, the article provides an analysis of the theoretical foundations of CSR, an assessment of its impact on key aspects of employee activity, and the development of recommendations for managers on creating a socially oriented and ethically balanced managerial environment that promotes employee development and supports the achievement of the organization's strategic goals.The article generalizes theoretical approaches to understanding corporate social responsibility as a factor influencing employee performance in the context of modern business practices. It systematizes scientific views on the interrelation between socially responsible company behavior and key employee performance indicators such as motivation, loyalty, productivity, and engagement. Based on the analysis of current managerial practices, it is determined that the integration of CSR into HR management strategies contributes to the formation of a positive socio-psychological climate, strengthens corporate culture, and increases the competitiveness of the enterprise. The article also summarizes managerial tools that ensure an effective combination of social responsibility and HR policy, and provides practical recommendations for improving such approaches within organizations.
Keywords: corporate social responsibility; employee performance; human resource management; corporate ethics; employee motivation; engagement; corporate culture; stakeholders; CSR strategy; employee emotional well-being